Combined Orthodontic and Surgical Approach in the Correction of a Class III Skeletal Malocclusion with Mandibular Prognathism and Vertical Maxillary Excess Using Bimaxillary Osteotomy. (22nd December 2013) - Jose Cherackal, George; Thomas, Eapen; Prathap, Akhilesh
Abstract : For patients whose orthodontic problems are so severe that neither growth modification nor camouflage offers a solution, surgery to realign the jaws or reposition dentoalveolar segments is the only possible treatment. Surgery is not a substitute for orthodontics in these patients. Instead, it must be properly coordinated with orthodontics and other dental treatments to achieve good overall results. Dramatic progress in recent years has made it possible for combined surgical orthodontic treatment to be carried out successfully for patients with a severe dentofacial problem of any type. This case report provides an overview of the current treatment methodology in managing a combination of asymmetrical mandibular prognathism and vertical maxillary excess.